INFLUENCE OF PROFITABILITY, SUSTAINABILITY FINANCE DISCLOSURES, AND SUSTAINABILITY REPORT ASSURANCE ON COST OF DEBT - Dhiva Oktantiani; Juniati Gunawan (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
This study tries to determine how financial openness affects sustainability and profitability, sustainability report assurance regarding the cost of debt, business age, and firm size as a measure of control. The population of this research consists of banking enterprises registered on the Indonesia Stock Exchange (IDX) between 2017 and 2021. This data is obtained from secondary data that comes from annual reports or sustainability reports has a 116-person sample size. This study's analytical method was text analysis regression analysis. double linear. According to this study's test findings, the profitability variable significantly and negatively affects the cost of debt. This demonstrates that sound financial sustainability has a negative and significant influence on the cost of debt when the variable sustainability financial disclosure is used. Disclosure might reduce borrowing costs. The sustainability report assurance variable has a detrimental and substantial influence on debt's cost. The age of the firm, which served as the study's control variable, produced negative findings and had no impact about the price of debt. The size of the business is the second controlling factor, which has been shown to have a favorable and considerable influence on the company's debt costs.